2008
DOI: 10.1111/j.1365-2583.2007.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inhibitors and substrates of Anopheles gambiae CYP6Z2

Abstract: Three CYP6Z genes are linked to a major pyrethroid resistance locus in the mosquito Anopheles gambiae. We have expressed CYP6Z2 in Escherichia coli and produced a structural model in order to examine its role in detoxification. E. coli membranes co-expressing CYP6Z2 and An. gambiae P450 reductase (AgCPR) catalysed the dealkylation of benzyloxyresorufin with kinetic parameters K(m) = 0.13 microM; K(cat) = 1.5 min(-1). The IC(50) values of a wide range of compounds were measured. Pyrethroids cypermethrin and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 26 publications
4
93
0
Order By: Relevance
“…The Drosophila melanogaster P450, CYP6g1, is associated with resistance to neonicotinoids, the organophosphate malathion and organochlorines DDT and methoxychlor (35)(36)(37)(38). Cross-resistance is arguably an unexpectedly infrequent observation, given the broad substrate specificity of P450s to, for example, plant toxins (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila melanogaster P450, CYP6g1, is associated with resistance to neonicotinoids, the organophosphate malathion and organochlorines DDT and methoxychlor (35)(36)(37)(38). Cross-resistance is arguably an unexpectedly infrequent observation, given the broad substrate specificity of P450s to, for example, plant toxins (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…CYP6Z2 was highly over-expressed in a pyrethroidresistant strain (Müller et al, 2007), but opposite to CYP6M2, was down-regulated in the midgut of A. gambiae at day 1 and day 11 after an infected blood meal (Félix et al, 2010). These results suggest a different role for CYP6Z2 in response to the insecticide and to parasite infection, however, we have to take into account that, although being able to bind to permethrin and cypermethrin, CYP6Z2 does not metabolise these compounds (Mclaughlin et al, 2008). So the over-expression of CYP6Z2 in a pyrethroid-resistant strain might be associated with different processes other than insecticide resistance.…”
Section: Resultsmentioning
confidence: 85%
“…A subsequent study showed that CYP6Z2 displays broad substrate specificity, which may be associated with xenobiotics metabolism and detoxification (Mclaughlin et al, 2008). Despite, CYP6Z2 being able to bind to permethrin and cypermethrin, CYP6Z2 does not metabolise neither one of these insecticides (Mclaughlin et al, 2008). In 2008, Djouaka et al also identified several P450 cytochromes over-expressed in one or more pyrethroid resistant populations of A. gambiae.…”
Section: Anopheles Gambiae P450 Cytochromes and Insecticide Resistancementioning
confidence: 99%
See 2 more Smart Citations